2021
DOI: 10.1080/20430795.2021.1972789
|View full text |Cite
|
Sign up to set email alerts
|

Does excluding sin stocks cost performance?

Abstract: We examine the impact of excluding sin stocks on expected portfolio risk and return. Exclusions involve risk relative to the market and peers. We show how this tracking error can be translated into an equivalent loss in expected return, which is negligible at low tracking error levels, but not at higher levels. However, even modest ex ante tracking error levels may lead to sizable compoundedunderperformance ex post. Taking an asset pricing perspective we find that popular exclusions typically go against reward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Kempf and Osthoff (2007) also concluded that it is not possible to achieve significant abnormal returns by employing negative screening. Blitz and Swinkels (2021) also confirmed that excluding sin stocks involves risk related to market and peers, thus confirming the previous studies. Positive and best-in-class screening techniques deliver abnormal returns, the maximum being in the latter technique.…”
Section: The Investment Performance Of Srisupporting
confidence: 88%
“…Kempf and Osthoff (2007) also concluded that it is not possible to achieve significant abnormal returns by employing negative screening. Blitz and Swinkels (2021) also confirmed that excluding sin stocks involves risk related to market and peers, thus confirming the previous studies. Positive and best-in-class screening techniques deliver abnormal returns, the maximum being in the latter technique.…”
Section: The Investment Performance Of Srisupporting
confidence: 88%
“…This stance has a theoretical foundation in literature as well where actualized returns are inversely related to expected returns (Fama and French, 2002; Pástor and Stambaugh, 2001, 2009). Blitz and Swinkels (2021) also argue that excluding sin stocks can cost portfolio performance in terms of expected returns unless the gap is filled by stocks that have similar characteristics. The fact that our results during the COVID period indicate a small portion, if not outright exclusion, of sin stocks in the portfolio also points towards a similar scenario for the future.…”
Section: Resultsmentioning
confidence: 99%
“…The debate on the superiority of green vis-a-vis sin investments has continued unabated [Statman, 2000, Schroder, 2004, Cui, 2007, L opez et al, 2007, Fabozzi et al, 2008, Renneboog et al, 2008, Hong and Kacperczyk, 2009, Kim and Venkatachalam, 2011, P erez-Gladish et al, 2013, Nofsinger and Varma, 2014, Peylo and Schaltegger, 2014, Leite and Cortez, 2015, Junkus and Berry, 2015, Trinks and Scholtens, 2017, Garvey et al, 2018, Duran-Santomil et al, 2019, Chang et al, 2019, Bolton and Kacperczyk, 2021, Rehman et al, 2021, Aswani et al, 2022, Blitz and Swinkels, 2021, P astor et al, 2022, Vymyatnina and Chernykh, 2022.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These firms in sectors typically labelled as unethical, like stocks from alcohol, tobacco, and gambling industries, yield higher returns above the market average. A significant body of this literature supports the observation that sin stocks consistently deliver higher risk-adjusted returns compared to broader market indices, showing their unique position in the investment field (Bannier et al 2023;Blitz and Swinkels 2023;Han et al 2022). Investors are now creating their list of sin stocks for avoidance as they do not want to be involved in such unethical activities.…”
Section: Introductionmentioning
confidence: 82%